El Excentrico, 1968-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1968 [20 de mayo de 1968], No volume or issue number. Cover has the photo of the Marc Poche family walking on the streets.